1975
DOI: 10.3382/ps.0541422
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Particle Sizes of Oyster Shell and Limestone on Performance of Laying Leghorn Pullets

Abstract: Commercial strain cross Leghorn pullets were fed a basal diet and either ground limestone (GL), ground oyster shell (GOS), screened pullet size oyster shell (POS), screened hen size oyster shell (HOS) or screened coarse limestone (CL). All 1272 birds were fed 2.5% calcium from 20 to 60 weeks of age then some were placed on a 3.5% calcium diet to 68 weeks.Egg shell rigidity was greatest from birds supplied non-flour calcium sources as compared to the flour calcium sources. Shell deformation means over the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…As shown in Table 1, neither calcium source nor level of calcium in the laying hen diet had a statistically significant effect on egg weight, percent hen-day egg production, or feed conversion, which is in agreement with the studies conducted by Watkins et al (1977), Kuhl et al (1977), and Miller and Sunde (1975). Figure 1 shows a comparison of effects of hensized oyster shell versus pulverized calcium sources on egg weight.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Table 1, neither calcium source nor level of calcium in the laying hen diet had a statistically significant effect on egg weight, percent hen-day egg production, or feed conversion, which is in agreement with the studies conducted by Watkins et al (1977), Kuhl et al (1977), and Miller and Sunde (1975). Figure 1 shows a comparison of effects of hensized oyster shell versus pulverized calcium sources on egg weight.…”
Section: Resultssupporting
confidence: 90%
“…Various calcium sources, in both the pulverized and granulated form, have been examined for subsequent egg shell formation. Scott et al (1971), Miller and Sunde (1975), Watkins et al (1977), and Kuhl et al (1977) all reported that the substitution of large particle calcium for a portion of the pulverized supplemental calcium improved egg shell strength. Roland et al (1974) in three short 6-week studies and Muir et al (1975) in a 50-week study utilizing low producing laying hens (67% production) concluded that the large particles of calcium carbonate had no influence on egg shell quality if the birds were receiving adequate calcium.…”
Section: Introductionmentioning
confidence: 94%
“…However, different particle sizes limestone had no (P >0.05) effect on tibia bone ash and humerus breaking strength and -stress. Results of the present study is in accordance with that of Miller & Sunde (1975), Cheng & Coon (1990) and Guinotte & Nys (1991) who reported that larger particles limestone resulted in a higher tibia bone breaking strength than ground sources, especially during the later stages (>66 weeks of age) of production (Fleming et al, 1998b). The improvement in bone breaking strength by using larger particles limestone (Cheng & Coon, 1990;Guinotte & Nys, 1991) are mainly ascribed to the increased medullary bone content and the decreased loss of cancellous bone (Rennie et al, 1997;Fleming et al, 1998b).…”
Section: Resultssupporting
confidence: 91%
“…Renewed interest in this subject was evident early in the 1970's as a result of several reports indicating markedly improved egg shell breaking strength when hen-size oyster shell replaced a portion of the ground limestone in laying hen diets. Miller and Sunde (1975) presented an excellent review of the literature on this subject. Most of the past data indicate large particle size calcium supplements to be superior to ground or small particle size supplements.…”
Section: Introductionmentioning
confidence: 99%